Wadsworth-emmons reaction by using the fluorapatite catalyst: kinetic studies - Vishwakarma, Rakhi; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2023)
Wadsworth-Emmons reaction was successfully carriedout byusing the fluorapatite (FAP) catalyst. The reaction of 2-methoxybenzaldehydeand triethylphosphonoacetate using FAP afforded & alpha;,& beta;-unsaturatedester with 100% conversion and 80% selectivity. A kinetic model wasvalidated at different temperatures by Langmuir-Hinshelwood-Hougen-Watson(LHHW), and the absence of mass transfer resistance was verified bythe Weisz Prater criterion. The effect of different catalysts, temperature,catalyst loading, solvent, mole ratio, and speed of stirring was studied.The FAP catalyst was characterized by Fourier transform infrared spectroscopy,Brunauer-Emmett-Teller method, nitrogen adsorption-desorption,transmission electron microscopy, energy-dispersive X-ray spectroscopy,temperature programmed desorption (TPD-NH3), X-ray diffraction,and X-ray photoelectron spectroscopy. The FAP catalyst was found tobe stable up to three recycles with no loss in activity.

Kinetic model of hydrogenation of glucose to sorbitol on a Ni/Bentonite catalyst - Pandya, Harmitkumar; Vinod, Chathakudath Prabhakaran; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial and Engineering Chemistry Research, 2024)
In the present work, we studied the hydrogenation of glucose to sorbitol using a nickel/bentonite catalyst. The Ni/bentonite catalyst was prepared by the wet impregnation method and characterized by different methods to understand the catalyst surface morphology, surface area, metal content, pore size, etc. Different reaction parameters such as temperature, hydrogen pressure, metal loading, catalyst loading, and agitation speed were studied to achieve a glucose conversion of 96.8% and a sorbitol selectivity of 95.3%. The reusability test was performed to examine the stability of the catalyst. The kinetic models such as the Eley-Rideal and Langmuir-Hinshelwood-Hougen-Watson models were used to study the hydrogenation of glucose and activation energy required for the reaction.

Aldol Condensation of Furfural with Acetone by Using Mg-Al-O-t-Bu HT Catalyst and Kinetic Studies - Patil, Sneha; Kamble, Paresh; Vinod, Chathakudath Prabhakaran; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2025)
An environment-friendly method for producing jet fuel precursors involves the aldol condensation of biomass-derived chemicals. In this study, the condensation reaction between furfural and acetone was performed using a Mg-Al-O-t-Bu hydrotalcite (HT) catalyst, achieving a furfural conversion of 99% and a selectivity of 82% toward 4-(2-furyl)-3-buten-2-one (FAc). The kinetics of the process were evaluated using a Langmuir-Hinshelwood-Hougen-Watson (LHHW) model across a range of temperatures, and the model showed an excellent fit to the experimental data. The effect of different catalysts, reaction temperatures, catalyst loadings, molar ratios, and reaction times was systematically investigated. The Mg-Al-O-t-Bu HT catalyst was extensively analyzed through techniques such as XRD, XPS, FTIR, nitrogen adsorption-desorption measurements, and CO2-TPD. The catalyst exhibited excellent stability, maintaining its performance consistently across five successive reaction cycles with no notable decline in activity. These findings highlight the industrial relevance of Mg-Al-O-t-Bu HT as a robust and recyclable solid base catalyst for biomass upgrading, with strong potential for process scale-up in renewable fuel production.

Synthesis of glycolic acid from glyoxal by using hydrotalcite catalyst and kinetic studies - Pandya, Harmitkumar N.; Kamble, Paresh A.; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (ChemCatChem, 2025)
In this work, Mg-Al hydrotalcite catalysts with different molar ratios were prepared using the co-precipitation method for the synthesis of glycolic acid (GA) from glyoxal. Various reaction parameters such as catalyst molar ratio, time, temperature, catalyst loading, and catalyst poisoning were studied and optimized for better conversion of glyoxal selectively to glycolic acid. Hydrotalcite catalyst with a 2:1 molar ratio of Mg: Al gives 98% conversion of glyoxal with 96% selectivity of glycolic acid at 100 degrees C temperature, 40% catalyst loading, and water as solvent in 8 h. Different characterization methods were used such as XRD, XPS, SEM-EDX, nitrogen adsorption desorption, and CO2-TPD for hydrotalcite catalyst. A kinetic study was also performed to observe the reaction order and activation energy required for the reaction.
Keywords: Glycolic acid; Glyoxal; hydrotalcite; kinetics

W/HAP catalyzed terpenic alcohols oxidation: kinetic studies - Poman, Aishwarya; Kamble, Paresh; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Reaction Chemistry & Engineering, 2025)
The selective oxidation of natural alcohols into carbonyl derivatives is a pivotal transformation in synthetic organic chemistry and industrial applications. This study focuses on the oxidation of borneol, a bicyclic secondary terpenic alcohol, into camphor using a tungsten-exchanged hydroxyapatite (W/HAP) catalyst and hydrogen peroxide as a green oxidant. Hydroxyapatite was synthesized via co-precipitation and functionalized with sodium tungstate to create the W/HAP catalyst, which was characterized using techniques such as SEM, EDS, TPD, XPS, and N2 adsorption-desorption to evaluate its surface morphology, porosity, and chemical composition. Oxidation reactions were conducted under optimized conditions, employing dimethylacetamide (DMA) as a solvent to achieve maximum conversion and selectivity. The W/HAP catalyst demonstrated superior performance, achieving nearly 99% conversion of borneol with 100% selectivity for camphor. Reaction parameters, including temperature, reactant stoichiometry, solvent choice, and catalyst loading, were systematically investigated. Higher reaction temperatures and oxidant concentrations favoured rapid conversion while maintaining high selectivity. Solvent effects revealed that DMA stabilized peroxo-tungstate intermediates, enhancing reaction efficiency compared to other solvents. Kinetic studies confirmed a first-order reaction mechanism with respect to borneol, and the activation energy was determined to be 44.23 kJ mol-1, highlighting the catalytic efficiency of W/HAP. Reusability tests confirmed the stability of the W/HAP catalyst over multiple cycles with minimal tungsten leaching. The methodology was extended to other terpenic alcohols, with varying degrees of success, emphasizing the substrate-specific activity of the catalyst. This work underscores the potential of tungsten-based heterogeneous catalysts in sustainable alcohol oxidation and highlights the industrial relevance of camphor synthesis as a renewable and eco-friendly approach to produce fine chemicals, fragrances, and pharmaceuticals.